PSYCHOLOGICAL EFFECTS OF COLORS AND COLOR THERAPY: रंगों का मनौवैज्ञानिक प्रभाव एवं रंग चिकित्सा - Sharma, Indu; Bisaria, Anjuli (International Journal of Research -GRANTHAALAYAH, 2014)
Everything in the universe has color. Color has a natural connection with human life. From birth to death, human life is visible only between colors. Every composition of nature, whether it is the sun, the earth, the sky or the tree has some color. It is visible to us only because of the color of the objects in the ground. The medium for experiencing color is light, which is reflected from the object and reaches our axon. Therefore, due to change of light or due to less or more amount of light, objects of the same color appear differently. The colors are seen in bright light and do not appear in dim light. In the light of red color, even white objects look red and green color looks black. That is, the color change is visible even if there is no change in the color arrangement due to the amount of light and the variation of the atmosphere at different places. The experience or color perception of colors is an important aspect of our visual experience. It is through light rays that we see the color of the object. The light that falls on an object dissolves into it, and something is reflected and reaches our axis. In the side of the axilla, there are microscopic fibrils called rhodes and canes, through which the color of the object is experienced by waves reflected from the object. The sensation of black and white colors is felt by Rhodes and the colors of yellow, blue, red green etc. are felt by canes. The red and green colors are visible by one set of cans and yellow, blue by another set. That is why the eyes do not get tired quickly when looking at green and red together or yellow and blue together. सृष्टि की प्रत्येक वस्तु में रंग है। मानव जीवन से रंग का नैसर्गिक सम्बन्ध है। जन्म से लेकर मृत्यु तक मानव जीवन रंगों के मध्य ही दृष्टिगोचर होता है। प्रकृति की प्रत्येक रचना चाहे वह सूर्य हो धरणी हो, आकाश हो या वृक्ष हो कोई न कोई रंग लिये हुये हैं। वस्तुओं के धरातल में रंग होने के कारण ही वह हमें दिखाई देती है। रंग के अनुभव का माध्यम प्रकाश है, जो वस्तु से प्रतिबिम्बित होकर हमारे अक्षपटल तक पहुॅंचता है। अतः प्रकाश के परिवर्तित होने से अथवा प्रकाश की मात्रा कम या अधिक होने से एक ही रंग की वस्तुएॅं अलग-अलग दिखाई पड़ती हैं। तेज प्रकाश में जैसी रंगते दिखाई पड़ती हैं धुंधले प्रकाश में वैसी नहीं दिखाई पड़ती। लाल रंग के प्रकाश में सफेद वस्तुएॅं भी लाल दिखती हैं तथा हरा रंग काला दिखता है। अर्थात् विभिन्न स्थानों पर प्रकाश की मात्रा तथा वातावरण की भिन्नता के कारण रंग व्यस्था में परिवर्तन नह ोने पर भी रंग परिवर्तन दिखाई पड़ता है।रंगों का अनुभव या वर्ण बोध हमारे दृश्यात्मक अनुभव का महत्वपूर्ण पक्ष है। प्रकाश किरणों के द्वारा ही हम वस्तु के रंग को देखते हैं। जो प्रकाश किसी वस्तु पर पड़ता है वह कुछ तो उसमें समा जाता है और कुछ प्रतिबिम्बित होकर हमारे अक्षपटल पर पहुॅंचता है। अक्षपटल के पाश्र्व में रोड्स और काॅन्स नामक सूक्ष्म तन्तु ग्रन्थियाॅं होती हैं जिनके द्वारा वस्तु से प्रतिबिम्बित तरंगों द्वारा वस्तु का वर्ण अनुभव होता है। काले व सफेद रंग की अनुभूति रोड्स द्वारा और पीला, नीला, लाल हरा आदि रंगों की अनुभूति काॅन्स द्वारा होती है। लाल व हरा रंग काॅन्स के एक सेट द्वारा तथा पीला, नीला दूसरे सेट द्वारा दिखाई पड़ता है। इसीलिये हरा व लाल एक साथ देखने या पीला नीला एक साथ देखने से आंखें शीघ्र नहीं थकती।